2021
DOI: 10.3390/microorganisms9071359
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Zone and Soil Properties Determine the Biodiversity of the Soil Bacterial Communities Associated to Native Plants from Desert Areas of North-Central Algeria

Abstract: Algeria is the largest country in Africa characterized by semi-arid and arid sites, located in the North, and hypersaline zones in the center and South of the country. Several autochthonous plants are well known as medicinal plants, having in common tolerance to aridity, drought and salinity. In their natural environment, they live with a great amount of microbial species that altogether are indicated as plant microbiota, while the plants are now viewed as a “holobiont”. In this work, the microbiota of the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The change in microbiota composition in the mixed hygrophile zone is not surprising. Other studies have shown how the soil microbiome response differed significantly based on the vegetation coverage, such as pine forest ( 60 ), evergreen broad-leaf forest, coniferous forest, subalpine dwarf shrubs, alpine meadows ( 61 ), and different native plants in desert areas ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The change in microbiota composition in the mixed hygrophile zone is not surprising. Other studies have shown how the soil microbiome response differed significantly based on the vegetation coverage, such as pine forest ( 60 ), evergreen broad-leaf forest, coniferous forest, subalpine dwarf shrubs, alpine meadows ( 61 ), and different native plants in desert areas ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Below-ground microbes comprise a large portion of global terrestrial ecosystem life’s genetic diversity and support important ecosystem functions and services, such as biomass production, nutrient cycling, and decomposition of organic matter [ 10 , 12 , 13 ]. Additionality, soil microorganisms are an essential link between the above-ground and below-ground components of terrestrial ecosystems [ 14 , 15 , 16 , 17 ]. Bacteria and fungi constitute vital parts of the soil microbiome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, assembly of the rhizosphere soil and bark microbiota was predominantly shaped by environmental factors and not by genotype or compartment niche ( Table 1 ). Environmental factors are generally accepted to be closely related to the composition of plant-associated microbiota ( Breidenbach et al, 2015 ; Trivedi et al, 2020 ; Zhang et al, 2020 ; Bona et al, 2021 ). Relative humidity was significantly correlated with the diversity index of the soil and bark bacterial communities, which was consistent with previous studies ( Dong et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%